Factores que inciden en la implementación de una planta doméstica para mejorar la calidad de agua potable en un sector emergente del cantón Babahoyo año 2018 - Molina Barbotó, Víctor Andrés (2019)
The present research it was executed in an emerging sector of the city of Babahoyo called "Black Gate" consisting of the manufacture of two designs of water purification plants at home, to determine the best treatment, and thus achieve improve the quality of water distributed by the Municipal Environmental Sanitation Company of Babahoyo, EMSABA SA, these designs are structured in two sections, the first, the Aluminum Sulphate prefiltered unit and the second design has Zeolite, in the second section as filtering unit the first design presents gravel, sand and activated carbon, while the second has Calcium and Sodium Hypochlorite. In the study, a total of 15 water samples were collected, which were structured as follows: (a) five samples of raw water (water that enters the plants); (b) five samples of water treated by a first design; (c) five water samples treated by a second design. The water samples were collected and transported in accordance with the INEN 1108 standard and processed in the laboratory using the methodologies described in "Standard Methods for the Examination of Water and Wastewater". For the physico-chemical and microbiological samples of water quality, a principal component analysis was applied to identify the most important parameters (variation). One and two samples from Man U. Whitman and Wilcoxon were applied to the most relevant parameters. , respectively. This corroborated that the best treatment was obtained by design number 1, because it presented the most optimal levels in terms of water quality. The results of the criterion of the people of Puerta Negra, their results were analyzed by descriptive analysis of cumulative frequency, in addition an analysis of ACP main components was applied, which was aimed at identifying the questions with the greatest response variation. Keywords: Designs, water, treatment, coagulant, flocculant.